Pelatihan Pembuatan Website Menggunakan Google Sites Pada Guru Bidang Kewirausahaan - Andrian Syahputra; Rizki Maulida (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This activity aims to implement the Tri Darma of Higher Education, as well as assist teachers at the Budi Agung Vocational High School in the field of Entrepreneurship studies in making websites for free using Google Sites, to improve the results of entrepreneurship activities taught to students so they can promote them online free of charge Hosting and Domian, because creating a website requires a high cost, especially for educational activities, with this training teachers can increase their knowledge in managing marketing content so they can compete in the digital era as promotional and marketing materials.